The judicial courts understanding of the united nations convention on contracts for the international sale of goods and the UNIDROIT principles of international commercial contracts: analysis of the colombian case and its high courts - López Pito, Isabel; Castro Quintero, Pablo; Camayo Ortiz, Sebastian (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The Convention on Contracts for the International Sale of Goods (CISG) and the UNIDROIT Principles of International Commercial Contracts (UNIDROIT Principles) are two essential instruments on international agreements. The highest Colombian judicial courts (the State Council, the Constitutional and Supreme Courts) acknowledge its significance. However, it is necessary to ensure the proper understanding of the articles and dispositions stated in both the CISG and the UNIDROIT Principles by the most important Colombian judicial courts. Therefore, this manuscript analyzes these instruments comprehension in related judicial decisions and its comparison with the literature.
Keywords: International agreements; Colombia; CISG; UNIDROIT Principles of International Commercial Contracts; United Nations Convention on Contracts for the International Sale of Goods